Global Branding Roadmap: identificação dos fatores determinantes e proposição de um modelo conceitual para a gestão estratégica de marcas em âmbito global - Rodrigues, Erlana Castro (2015)
Decisions on the international branding strategy are among the most researched themes in global branding, but there is no predominant theoretical framework that guides research in this academic field, nor in its management practice. The present study aims to propose a conceptual model for global brand management based on the identification of the critical factors that influence this activity. To reach the proposed goal the research is divided into two stages. In the deductive stage a systematic review of the most cited articles in the field of global branding is carried out to identify the determining factors 'a priori'. At the inductive stage, 14 experienced global brand managers of different nationalities are interviewed in order to identify critical factors that emerge from their perspective and practice. Confronting literature with management practice, it is also possible to conclude that main theoretical principles of global branding are still valid and under discussion; even though globalization‘s current phase is presenting a much more complex business environment than it was predicted 30 years ago, when the theoretical foundations of this field were created. The main contribution of this study is the establishment of a relationship between internal and external determinant factors and its influence on the global management of brands. The aim is to contribute to the formulation of a theory on Global Branding.